2009
DOI: 10.1186/1471-2350-10-99
|View full text |Cite
|
Sign up to set email alerts
|

Genetic association study of selected candidate genes (ApoB, LPL, Leptin) and telomere length in obese and hypertensive individuals

Abstract: Background: A genetic study was carried out among obese and hypertensive individuals from India to assess allelic association, if any, at three candidate loci: Apolipoprotein B (ApoB) minisatellite and two tetranucleotide repeat loci; LPL (Lipoprotein lipase) and Leptin. Attempt has also been made to find out whether telomere length attrition is associated with hypertension and obese individuals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 62 publications
2
18
0
Order By: Relevance
“…The predominant genotype was 152/152 in obese subjects with a frequency of 0.114 compared to the genotype 152/156 in normal subjects with a frequency of 0.135. (41) Agreeing with our results, they have found that in obese individuals, the frequency of genotype II/II was significantly higher as compared to normal and hypertensive individuals, genotype I/II had a significantly higher frequency in obese group as well compared to normal and hypertensive group. (41) In another study done by Moffett et al, among African American subjects, they reported a wide heterogeneity of the leptin gene tetranucleotide repeat alleles being classified into three classes; type 1 alleles (146-178 bp); type 2 alleles (165 and 193 bp) and type 3 alleles (210 and 254 bp).…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…The predominant genotype was 152/152 in obese subjects with a frequency of 0.114 compared to the genotype 152/156 in normal subjects with a frequency of 0.135. (41) Agreeing with our results, they have found that in obese individuals, the frequency of genotype II/II was significantly higher as compared to normal and hypertensive individuals, genotype I/II had a significantly higher frequency in obese group as well compared to normal and hypertensive group. (41) In another study done by Moffett et al, among African American subjects, they reported a wide heterogeneity of the leptin gene tetranucleotide repeat alleles being classified into three classes; type 1 alleles (146-178 bp); type 2 alleles (165 and 193 bp) and type 3 alleles (210 and 254 bp).…”
Section: Discussionsupporting
confidence: 88%
“…(41) Agreeing with our results, they have found that in obese individuals, the frequency of genotype II/II was significantly higher as compared to normal and hypertensive individuals, genotype I/II had a significantly higher frequency in obese group as well compared to normal and hypertensive group. (41) In another study done by Moffett et al, among African American subjects, they reported a wide heterogeneity of the leptin gene tetranucleotide repeat alleles being classified into three classes; type 1 alleles (146-178 bp); type 2 alleles (165 and 193 bp) and type 3 alleles (210 and 254 bp). They attributed the failure of some population-based studies to detect association between measures of obesity and the leptin gene-(TTTC) locus to be due to this wide heterogeneity.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations